2015
DOI: 10.3109/00016357.2015.1030768
|View full text |Cite
|
Sign up to set email alerts
|

The effects of periodontal therapy on serum and salivary leptin levels in chronic periodontitis patients with normal body mass index

Abstract: Altered concentrations of leptin in serum and saliva are observed in CP patients which can be restored in favor of health after periodontal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Further, the Galbraith plots showed that the studies performed by Shi et al, Purwar et al, Mendoza-Azpur et al, Thanakun et al, and Karthikeyan et al (L1) [30, 31, 49, 51, 52]; Mendoza-Azpur et al and Sete et al (A1) [16, 31]; and Purwar et al (L2) [57] were located outside of the two lines in the Galbraith plots of the subgroups of BMI <30. After removing the outliers, the heterogeneities effectively decreased, and the results were not materially changed in the subgroups of BMI <30 (L1: SMD = 0.796, 95% CI: 0.572–1.020, P  = 0.000; I 2  = 40.9, P  = 0.095; A1: SMD = −0.251, 95% CI: −0.408 to −0.095, P  = 0.002; I 2  = 13.6, P  = 0.323; L2: SMD = −0.162, 95% CI: −0.417 to 0.094, P  = 0.215; I 2  = 0.0, P  = 0.556).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the Galbraith plots showed that the studies performed by Shi et al, Purwar et al, Mendoza-Azpur et al, Thanakun et al, and Karthikeyan et al (L1) [30, 31, 49, 51, 52]; Mendoza-Azpur et al and Sete et al (A1) [16, 31]; and Purwar et al (L2) [57] were located outside of the two lines in the Galbraith plots of the subgroups of BMI <30. After removing the outliers, the heterogeneities effectively decreased, and the results were not materially changed in the subgroups of BMI <30 (L1: SMD = 0.796, 95% CI: 0.572–1.020, P  = 0.000; I 2  = 40.9, P  = 0.095; A1: SMD = −0.251, 95% CI: −0.408 to −0.095, P  = 0.002; I 2  = 13.6, P  = 0.323; L2: SMD = −0.162, 95% CI: −0.417 to 0.094, P  = 0.215; I 2  = 0.0, P  = 0.556).…”
Section: Resultsmentioning
confidence: 99%
“…Besides this, nine clinical trials detecting the serum levels of leptin and adiponectin in patients with periodontitis before and after periodontal treatments were included [28, 29, 39, 54–59]. The clinical trials performed by Duzagac et al, Purwar et al, and Shimada et al also enrolled the periodontally healthy groups and provided the pretherapy data on the serum levels of leptin and adiponectin in patients with periodontitis and healthy individuals [54, 57, 58]. The studies performed by Altayet al, Duzagacet al, Goncalveset al, Mendoza-Azpuret al, and Zimmermann et al provided the data on subjects with BMI <30 and BMI ≥30 separately [31, 32, 39, 54–56], and the study performed by Zeigler et al provided only the data on obesity subjects.…”
Section: Resultsmentioning
confidence: 99%
“…In the two Purwar studies [20,21] and the Karthikeyan study [18], CP was defined for each patient by plaque index, gingival index, pocket depth, and clinical level of periodontal attachment that were scored on six sites (mesiovestibular, vestibular, distovestibular, mesiolingual, lingual, and distolingual) in each tooth, excluding the third molar, and the presence of bleeding during probing was evaluated using a sterile periodontal probe. All clinical parameters were recorded by one independent person.…”
Section: Description Of Selected Studies For Quantitative Analysismentioning
confidence: 99%
“…The diagnosis of CP was established on the basis of clinical findings of gingival inflammation, clinical loss of periodontal attachment of >5 mm for Purwar [20,21] and only >1 mm for Karthikeyan [19], pocket depth of ≥4 mm in 3-4 sites in >4 teeth in each quadrant, and radiographic evidence of bone loss.…”
Section: Description Of Selected Studies For Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation